ANALYSIS OF BANK HEALTH LEVELS USING THE RGEC METHOD AT PT BANK PERMATA TBK - Tommy Kuncara; Rini Dwiastutiningsih (Asosiasi Dosen Muda Indonesia, 2023)
This research aims to find out the health level of Bank Permata. The type of research used is descriptive research with a quantitative approach. The variables used are Risk Profile which is measured by the NPL and LDR ratio, Good Corporate Governance (GCG) which is measured through self-assessment results, Earnings which is measured through the ROA ratio, and Capital which is measured through the CAR ratio. PT Bank Permata was included in composite rating category 1, which reflects the bank's very healthy condition, so it is considered very capable of facing significant negative influences from changes in business conditions and other external factors. Calculations based on the risk profile using the NPL and LDR ratios show a healthy category. The Good Corporate Governance (GCG) assessment is included in the very healthy category. Earnings assessment using the ROA ratio is stated in the quite healthy category. And for the assessment based on Capital using the CAR ratio, it is stated in the very healthy category.